WATER EXTRACT OF PURPLE SWEET POTATO TUBERS REDUCES BLOOD PRESSURE 0F HYPERTENSIVE RATS INDUCED BY NaCl - JAWI, I MADE; SUTIRTA YASA, I W. P. (Medicina, 2013)
Compliance of hypertensive patients to take medication is one of many determinant factors to achieve successful treatment. Side effects and the expensive price of drugs are the causes of the incompliance of patients taking the medication. Utilization of herbal medicine is a new hope to resolve the issue. Purple sweet potato tuber is a plant part that expected has beneficial effect in lowering blood pressure because it contains anthocyanins which are antioxidants and can preserve endothelial function. To prove these hypothesis, a study was conducted with randomized control group pre and post-test design. The  study was done on 20 adult male Wistar rats that were divided into two groups of 10 rats.  Both groups of rats were made hypertensive by administering high doses of NaCl. Control group of rats given only NaCl alone for 14 days. Treatment group were given NaCl and water extract of purple sweet potato tuber with a dose of 4 cc per day for 14 days. Before treatment and during treatment, blood pressure were taken everyday with special sphygmomanometer. The results indicate a significant difference in blood pressure between the control group with treatment (P = 0.0001). In the treatment group, it was observed that there was a significant decrease in blood pressure compared to the control group (P=0.0001). From the results of this study, it can be concluded that administration of purple sweet potato tuber water extract may lower high blood pressure of rats induced by NaCl.
Keywords: sweet purple potato tuber, blood pressure, hypertensive rats